(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud computing is a computing technique where sharing of resources rather than personal system or servers for applications. Cloud is used as a metaphor for Web applications. Cloud computing is a web based computing such as database, server applications etc. Main goal of cloud computing is high performance computing power. Virtualization is a technique to improve computing power. This paper aim a relative study on different frameworks used in cloud computing